The HITRAP facility for slow highly charged ions. (26th November 2015) - Herfurth, F; Andelkovic, Z; Barth, W; Chen, W; Dahl, L A; Fedotova, S; Gerhard, P; Kaiser, M; Kester, O K; Kluge, H-J; Kotovskiy, N; Maier, M; et al.
Abstract: At the GSI accelerator complex, behind the universal linear accelerator UNILAC and the synchrotron SIS, highly charged ions up to are produced at 400 MeV/nucleon. When this beam is sent through a copper foil all or nearly all remaining electrons are stripped. The HITRAP facility, a combination of a linear decelerator and a cryogenic Penning trap, is built to decelerate those ions to almost rest and to provide them for the experiments. In a number of commissioning beam times, the deceleration in the ESR, the extraction, bunching and, finally, deceleration to 6 keV/nucleon has been shown. The remaining steps, being capture and cooling in a cryogenic Penning trap, are presently tested off-line.